Playing With Antidepressants: Perspectives From Indian Australians and Anglo-Australians Living With Depression - Brijnath, Bianca; Antoniades, J. (Sage Publications, 2016)
Patient perspectives were explored on the meaning and experience of antidepressant use by applying Johan Huizinga's theory of play to interviews from Indian Australians and Anglo-Australians diagnosed with depression. Through the analysis, the centrality of Huizinga's "magic circle" emerged, that is, defining the boundaries within which one could safely play. Consumption of antidepressants involved learning, breaking, and modulating rules of the game of adherence, then forging a new "magic circle." In these games, there were playful elements including experimentation, improvisation, absorption, and experiential learning. This application of Huizinga's theory in relation to antidepressant use is a novel approach in the literature on medication non/adherence. This application not only opens a new theoretical line of inquiry but also shows that antidepressant non/adherence is not a static practice but dynamic and changing, revealing critical insights around participant's agency, capabilities, desires, and notions of selfhood with regard to managing their depression and conceptualizing their recovery.